2011
DOI: 10.1016/j.juro.2010.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Renal Cell Carcinoma With Bone Metastasis: Who Are the Long-Term Survivors?

Abstract: Our risk classification incorporating 5 risk factors enables accurate prediction of survival, which can be helpful to make clinical decisions in cases of renal cell carcinoma with bone metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 14 publications
2
33
0
4
Order By: Relevance
“…Survival is especially short in patients who have vertebral and extraosseous metastases. 14 The introduction of tyrosine kinase inhibitors in the last few years has not only increased the overall survival of patients with RCC, but it has also decreased the incidence of brain metastases. 23 Early studies showed that dose escalation for the treatment of radioresistant spine metastases may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Survival is especially short in patients who have vertebral and extraosseous metastases. 14 The introduction of tyrosine kinase inhibitors in the last few years has not only increased the overall survival of patients with RCC, but it has also decreased the incidence of brain metastases. 23 Early studies showed that dose escalation for the treatment of radioresistant spine metastases may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…After analyzing 94 patients, Kume et al identified another five risk factors for predicting the survival of RCC patients with BM, including RCC sarcomatoid differentiation, spinal involvement, extra-osseous metastases, alkaline phosphatase level >1.5 times the normal level, and C-reactive protein level >0.3 mg/dL 7. To summarize the clinical characteristics of metastatic RCC and to integrate the symptom-based survival predictive system, studies evaluating the risk factors and prognostic factors for BM in RCC patients are needed.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis has shown that elevated ESR levels were associated with poor overall survival (OS), cancer-specific survival (CSS), and recurrence-free survival (RFS) (Wu et al , 2011). Some studies, but not all (Magera et al , 2008), have observed that elevated ALP levels, a possible sign of paraneoplastic syndrome of RCC patients, were associated with poor RCC survival (Lee et al , 2006; Kume et al , 2011). …”
mentioning
confidence: 99%